Advances in myocardial CT perfusion imaging technology - Yi, Yan (Am J Transl Res, 2016)
With the booming development of CT technology, CT-based myocardial perfusion imaging (CTP) has begun to mature and has exhibited great advantages and application prospects as a complete evaluation method of anatomy and function for CAD. This article summarizes the CTP technology progress and analytical methods of CTP in recent years, briefly reviews the clinical relevance, and subsequently discusses the limitation and future development.